A breath after drowning - Blanchard, Alice (Titan Books, 2018)
Child psychiatrist Kate Wolfe's world comes crashing down when one of her young patients commits suicide, so when a troubled girl is left at the hospital ward, she doubts her ability to help. But the girl knows things about Kate's past, things she shouldn't know, forcing Kate to face the murky evidence surrounding her own sister's murder 16 years before, bringing Kate face to face with her deepest fear.